The association between use of nonsteroidal anti-inflammatory drugs (NSAIDs) and peptic ulcer/gastritis among outpatients, Srinagarind hospital, Khonkaen Province, Thailand - Tangbandit, Piyawan
A hospital-based case-control study was undertaken to determine the association between patterns of use of NSAIDs and peptic ulcer/gastritis among outpatients in OPD medicine Srinagarind Hospital, KhonKaen Province, Thailand.Data were obtained through interviews and review of medical records. Over a four-month period, there were 131 cases of pu/gastritis confirmed by endoscopy and 262 controls.The study sample was composed of 229 NSAIDs users of any dose and duration (101 cases and 128 controls). The sex ratio among cases was 147 and 145 among control. The distribution by age group shows that almost half (48.8) of cases and (52.3) controls belong to the 40-64 years of age group.In a multivariate analysis, the adjusted odds ratio of pu/gastritis associated with NDSAIDs use was 6.85[4.24-11.05]. The risk of having pu/gastritis was greater for prescribed use than self-medication use among PG-synthesis blocked type of NSAIDs users (18.34[2.94-114.40] 1.40[0.52-3.78]).Users of longer duration had 2 times the risk of having pu/gastritis than users of lower dose and shorter duration (2.31[0.80-6.63]). Self-medication NSAIDs use seemed to be protective against pu/gastritis, however, these associations were modified by type of NSAIDs and concomitant use of steroid drug.There was a strong association between multiple NSAIDs use with pu/gastritis (11.92[4.05-35.10]).Among prescribed users, there was a significant difference in concomitant use of steroid compared to non-steroid users. (105.51[6.70-1661.41]). There was also a significant difference in the concomitant use of steroid among self-medication NSAIDs users (3.13[1.14-8.60]).We conclude that, in this study, substantial risk of having pu/gastritis was associated with patterns of NSAIDs use and concomitant use of protective drug was protective against pu/gastritis (0.01[0.00-0.05]).Recommendations include starting NSAIDs treatment on short duration and use of single type of NSAIDs at a time; avoidance of concomitant use of cortiscoteroid drug and inclusion of protective drugs in the treatment regimen.The association between individual type of NSAIDs is recommended in future studies using a large sample size to be able to detect statistical interaction between two or more exposure variables.